AN ANALYSIS OF DIRECTIVE SPEECH ACTS USED IN THE ADDAMS FAMILY 2 MOVIE SCRIPT - Andrean, Rama Renaldi Nugroho Jersy; Nurhantoro, Tri Septa; Kristiawan, Yohanes Angie (JOLALI: Journal of Language and Literature, 2025)
The directive speech act refers to the utterance used by the speaker to ask and tell the speech partner to act. Therefore, speech and actions created through the phenomenon of directive speech acts can be found in human communication and language speech, such as in real life and movies. It can be seen through one of the movies such as The Addams Family 2. The Addams Family 2 is a movie that has many directive speech acts that occur in the script. The purpose of this research is to understand the classification of directive speech acts and understand why directive speech acts in the form of types and functions are used in The Addams Family 2 movie script. The researcher used a descriptive qualitative method in explaining the overall types and functions of directive speech acts on the data in the object of research. The analyzed movie is obtained from Apple TV (iTunes Channel) and the movie script comes from https://scrapsfromtheloft.com/movies/the-addams-family-2-transcript. The Addams Family 2 because when the characters have a conversation there are utterances that have the types of asking, commanding, offering, inviting, advising, prohibiting, encouraging, competitive, convivial, collaborative, and conflictive. The theory used in analyzing this research is the type of directive speech acts by Austin and Searle's theory as well as the function of speech acts by Leech's theory. The directive speech act of asking is the highest data which amounted to 84 data (49.41%). Each character's utterance ensures that the interlocutor can provide answers and information in accordance with the questions given because the speaker asks questions to speech partners to get answers and information. Based on the data analysis, the competitive directive speech act function is the highest data with 124 (72.94%). This is because the competitive aspect arises when there is competition between speakers and speech partners regarding how actions or requests should be made. However, the speech partner may have a desire that is contrary to the wishes of the speaker.